Intellectual progression of green service research: a bibliometric examination and avenues for future research - Oluwatobi A. Ogunmokun; Juliet E. Ikhide; Christian Nedu Osakwe; Abdul Bashiru Jibril (Cogent Social Sciences, 2024)
This article reviews the extant literature on green services based on data obtained from the Web of Science core collection database. The objective of the review is the identification of emerging and predominant themes, authors, and organizations within this domain of research. A bibliometric approach is taken in the analyses of the co-authorship, co-citations, keyword co-occurrence, and bibliographic coupling to assess the evolution of this research domain, based on a total of 212 publications. The results and visual representations of networks indicate that in the last decade, the major themes in green service research are ‘sustainability’, ‘impact’ and ‘performance’. Further, most of the studies have been published in the hospitality, supply chain and marketing fields. These and many more valuable insights discovered in this review present scholars and practitioners, among other things, a clearer understanding of the state-of- the art in green service research which could facilitate future studies and practices toward emerging issues in the field, such as big data and healthcare.